Prominent Asymmetric Muscle Weakness and Atrophy in Seronegative Immune-Mediated Necrotizing Myopathy - Sunha Park (MDPI AG, 2021)
Immune-mediated necrotizing myopathy, a new subgroup of inflammatory myopathies, usually begins with subacute onset of symmetrical proximal muscle weakness. A 35-year-old male presented with severe asymmetric iliopsoas atrophy and low back pain with a previous history of left lower extremity weakness. Although his first left lower extremity weakness occurred 12 years ago, he did not receive a clear diagnosis. Magnetic resonance imaging of both thigh muscles showed muscle edema and contrast enhancement in patch patterns, and the left buttock and thigh muscles were more atrophied compared to the right side. Serum creatine kinase levels were elevated, and serologic testings were all negative. Genetic testing using a targeted gene-sequencing panel for neuromuscular disease including myopathy identified no pathogenic variants. Muscle biopsy on the right vastus lateralis showed scattered myofiber necrosis with phagocytosis and an absence of prominent inflammatory cells, consistent with seronegative necrotizing myopathy. Thus, unusual asymmetric muscle weakness and atrophy can be a manifestation of inflammatory myopathy.